2020
DOI: 10.1101/2020.05.11.20096263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reappearance of Effector T Cells Predicts Successful Recovery from COVID-19

Abstract: 2 7

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The drop in lymphocytes included γδ T cells, which were highly reduced in the circulation compared with healthy controls, especially the Vδ2 subset. This has also been reported by other studies ( 72 74 ). Lei et al., showed that the γδ T cells remaining in the blood had a CD25+ activated phenotype, although the very early activation marker CD69 did not increase compared to healthy controls, which the authors suggested may be because this marker was expressed earlier in infection ( 72 ).…”
Section: Gamma Delta T Cellssupporting
confidence: 91%
See 1 more Smart Citation
“…The drop in lymphocytes included γδ T cells, which were highly reduced in the circulation compared with healthy controls, especially the Vδ2 subset. This has also been reported by other studies ( 72 74 ). Lei et al., showed that the γδ T cells remaining in the blood had a CD25+ activated phenotype, although the very early activation marker CD69 did not increase compared to healthy controls, which the authors suggested may be because this marker was expressed earlier in infection ( 72 ).…”
Section: Gamma Delta T Cellssupporting
confidence: 91%
“…Odak et al., showed a striking reduction in effector memory cells within the γδ T cell population, and an increase in naïve cells, and suggested that the effector memory γδ T cells may be recruited to the lungs. They also theorized that the reappearance of effector cells in the blood was associated with recovery from COVID-19 ( 74 ).…”
Section: Gamma Delta T Cellsmentioning
confidence: 99%
“…For example, Laing et al . partnered a total lymphocyte count from a full blood count and flow cytometry to derive estimates of absolute T cell subset counts based on the gated percentages [ 54 ], while other studies used direct quantification of lymphocyte subsets, such as TruCount™ [ 58 ]. A majority of the studies used either recognised or in-house flow cytometry tools.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, characterization of T-Cell epitope (certain region of SARS-CoV-2 virus which T-cell utilizes in immune response) and B-cell epitope (certain region of SARS-CoV-2 virus which B-cell utilizes in immune response) has been attempted by researchers. [163] From chemistry point of view, mapping of viral epitopes is identifying (a) the region from a long protein molecule (amino acid chain) and (b) amino acids sequence in those region. At molecular levels these epitope site will make connecting bonds/interactions with another macromolecule either a Y-shaped protein molecule or any other immune cell.…”
Section: Vaccinementioning
confidence: 99%